2007
DOI: 10.1172/jci28769
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative stress mediates tau-induced neurodegeneration in Drosophila

Abstract: Markers of oxidative damage have been detected in brain tissue from patients with Alzheimer disease (AD) and other neurodegenerative disorders. These findings implicate oxidative injury in the neurodegenerative process, but whether oxidative stress is a cause or a consequence of neurotoxicity remains unclear. We used a Drosophila model of human tauopathies to investigate the role of oxidative stress in neurodegeneration. Genetic and pharmacological manipulation of antioxidant defense mechanisms significantly m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
228
0
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 280 publications
(238 citation statements)
references
References 64 publications
9
228
0
1
Order By: Relevance
“…Thus, although in our model cell cycle activation and neuronal death depend on tau phosphorylation (Khurana Dias-Santagata et al, 2007;Fulga et al, 2007;Steinhilb et al, 2007), our data indicate that blocking phosphorylation at restricted sites still induces neurotoxicity that is mediated by TOR signaling and cell cycle activation. These findings strongly suggest that individual SP/TP mutants induce neurodegeneration by the same mechanisms as wild-type tau.…”
Section: Neurotoxicity Induced By Sp/tp Tau Mutants Is Mediated By Tomentioning
confidence: 54%
See 1 more Smart Citation
“…Thus, although in our model cell cycle activation and neuronal death depend on tau phosphorylation (Khurana Dias-Santagata et al, 2007;Fulga et al, 2007;Steinhilb et al, 2007), our data indicate that blocking phosphorylation at restricted sites still induces neurotoxicity that is mediated by TOR signaling and cell cycle activation. These findings strongly suggest that individual SP/TP mutants induce neurodegeneration by the same mechanisms as wild-type tau.…”
Section: Neurotoxicity Induced By Sp/tp Tau Mutants Is Mediated By Tomentioning
confidence: 54%
“…We showed that blocking phosphorylation of all 14 SP/TP sites in tau by mutating them to alanine markedly inhibited tau-induced neurodegeneration in Drosophila Steinhilb et al, 2007). Conversely, mutation of all SP/TP sites to glutamate generated the pseudophosphorylated tau E14 construct, which is significantly more toxic than tau WT (Khurana et al, 2006;Dias-Santagata et al, 2007;.…”
Section: Introductionmentioning
confidence: 94%
“…Biochemical pathways that are affected in neurodegenerative conditions, such as detoxification, protein clearance, and immunological and stress responses, are conserved between flies and humans (reviewed in Marsh and Thompson 2006). Indeed, analysis of Drosophila models of Huntington's and other expanded polyglutamine-caused conditions (Tsuda et al 2005;Bilen et al 2006), as well as Parkinson's (Scherzer et al 2003;Auluck et al 2005;Kontopoulos et al 2006) and tau-related diseases ( Jackson et al 2002;Mudher et al 2004;Dias-Santagata et al 2007;Fulga et al 2007), has yielded important insight into pathways of neurodegeneration.…”
mentioning
confidence: 99%
“…Among the kinases known to phosphorylate tau, JNK and their phosphorylated and thus activated forms decreased with longer treatment periods (Figs S1 and 1A). These results were unexpected, as JNK is also known as stress-activated protein kinase (SAPK) (Zhu et al, 2004;Dias-Santagata et al, 2007). Phospho-JNK levels were increased in cells treated with H 2 O 2 (Fig.…”
Section: Resultsmentioning
confidence: 96%
“…By contrast, when cells are treated with hydrogen peroxide (H 2 O 2 ), ultraviolet light, menadione, or iron, tau phosphorylation decreases (Zhu et al, 2004). Chronic application of oxidative stress in neuronal cells, Drosophila, and mouse models of tauopathy through genetic manipulations induces neurodegeneration and tau accumulation (Zhu et al, 2004;Dias-Santagata et al, 2007;Kulic et al, 2009). Here, we used a chemical named alloxan to investigate the acute effects of oxidative stress on cellular and mouse models of tauopathy.…”
Section: Introductionmentioning
confidence: 99%